1998
DOI: 10.1159/000018626
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Rupture of the Pancreaticoduodenal Artery: Three Cases

Abstract: We report 3 cases of spontaneous rupture of pancreaticoduodenal arteries (PDA). In the first case, an aneurysm of the PDA was demonstrated with stenosis of the celiac trunk; in the second case occlusion of the hepatic artery was shown. In both cases, arterial pancreatic arcades were enlarged and blood flow was retrograde from the superior mesenteric artery. Local high intravascular pressure due to retrograde blood flow through the arterial pancreatic arcades was thought to be the cause of aneurysm development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…Most patients start with nonspecific epigastric pain, but some other cases include debut as upper gastrointestinal bleeding due to rupture into the duct of Wirsung (also known as hemosuccum) or a more dramatic approach as massive hemoperitoneum due to rupture to free cavity, as our first case was, a really dramatic episode indeed with very high postoperative mortality figures (1,(5)(6)(7)(8).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Most patients start with nonspecific epigastric pain, but some other cases include debut as upper gastrointestinal bleeding due to rupture into the duct of Wirsung (also known as hemosuccum) or a more dramatic approach as massive hemoperitoneum due to rupture to free cavity, as our first case was, a really dramatic episode indeed with very high postoperative mortality figures (1,(5)(6)(7)(8).…”
Section: Discussionmentioning
confidence: 98%
“…Surgery has been traditionally the treatment employed to solve this entity, however nowadays endovascular aneurysm embolization is the treatment chosen up to 80% of cases (5,9), with different techniques depending on the material used (6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, there have only been two reports of a true PDA aneurysm associated with occlusion of the common hepatic artery, including the present case. 9 It has been suggested that stenosis or occlusion of the celiac axis might be related to the development of true PDA aneurysms. 9 Celiac axis stenosis or occlusion leads to the modification of blood flow through the pancreatic arcades, which supply the hepatic and splenic arteries from the superior mesenteric artery.…”
Section: Discussionmentioning
confidence: 99%
“…9 It has been suggested that stenosis or occlusion of the celiac axis might be related to the development of true PDA aneurysms. 9 Celiac axis stenosis or occlusion leads to the modification of blood flow through the pancreatic arcades, which supply the hepatic and splenic arteries from the superior mesenteric artery. Thus, blood flow might increase in the PDA and cause dilatation of this vessel with the eventual development of an aneurysm.…”
Section: Discussionmentioning
confidence: 99%